Sodium-ion battery positive electrode material and preparation method thereof

By preparing nanocomposite active substances and functional binders, the shortcomings of the positive electrode materials of sodium ion battery in terms of cycle stability, rate performance and specific capacity are solved, and the performance of the electrode materials is significantly improved and the service life is extended.

CN119650666APending Publication Date: 2025-03-18GUANGDONG RUICHI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510010781.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have shortcomings in terms of cycle stability, rate performance and specific capacity, and binders such as polyvinyl fluoride tend to lose their bonding ability in the electrolyte, affecting the performance of the electrode material.

Method used

By preparing nanocomposite active substances and functional binders, the nanocomposite active substances consist of nitrogen-rich sulfur porous carbon materials and 7,7,8,8-tetracyanoterephthalene dimethylamethane. The functional binders are obtained from polydopamine-grafted polyethylene oxide, and are used in combination to improve the performance of the electrode material.

Benefits of technology

It significantly improves the specific capacity, cycle stability and rate performance of the positive electrode material of sodium ion battery, slows down the solubility of organic compounds, enhances the conductivity and bonding strength, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650666A_ABST
    Figure CN119650666A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion batteries, and discloses a sodium-ion battery positive electrode material and a preparation method thereof.The sodium-ion battery positive electrode material comprises a nano-composite active substance, a conductive substance and a functional binder, and the nano-composite active substance is prepared by coating organic compounds 7, 7, 8, 9, 10, 11, 12, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13, 13 Compared with the prior art, the positive electrode material has the advantages that the positive electrode material is prepared from 7, 7, 8, 8-tetracyano-p-benzoquinone dimethane, so that the conductivity is enhanced, the number of active sites is increased, meanwhile, the dissolution of an organic compound 7, 7, 8, 8-tetracyano-p-benzoquinone dimethane in an electrolyte is effectively slowed down and inhibited, and the specific capacity, the cycling stability and the rate capability of the positive electrode material of the sodium-ion battery are improved; the functional adhesive is environment-friendly, has excellent adhesive property and ionic conductivity, and can reduce the phenomenon of interface stripping in the charge-discharge process; therefore, the sodium ion battery positive electrode material prepared by the invention has excellent cycling stability, rate capability and higher specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] The continuous consumption of fossil energy and the resulting environmental pollution have led to the rapid development of renewable energy. As a renewable energy source, electrochemical batteries are easy to use and have high energy conversion efficiency, and are being vigorously studied. Lithium-ion batteries are widely used in the field of batteries. As the demand for lithium gradually increases, the price of lithium continues to grow, but the limited reserves of lithium resources, uneven distribution and inconvenient access limit the application potential of lithium-ion batteries. Therefore, sodium, which is in the same main group as lithium, has similar physical and chemical properties to lithium, is low in price, has abundant reserves, is highly safe and environmentally friendly. Therefore, sodium-ion batteries have also become a research hotspot in the field of batteries.

[0003] Sodium ion batteries are mainly composed of positive electrodes, negative electrodes, separators, and electrolytes. The electrode materials are a mixture of active materials, binders, and conductive materials. The positive electrode materials of sodium ion batteries mainly include layered transition metal oxides, polyanion compounds, Prussian blue compounds, organic compounds, etc. Layered transition metal oxide sodium materials will cause structural phase changes when sodium ions are inserted and removed, resulting in poor cycle stability. Polyanion compounds have poor ionic conductivity and low volume energy density. Prussian blue compounds will cause environmental pollution during the preparation process and the finished product has poor thermal stability. Organic compounds are environmentally friendly, have abundant raw materials, and have good cycle performance and energy density, but their applications are limited because they are easily dissolved in electrolytes. Therefore, organic compounds can be improved and coated with materials to slow down or inhibit the dissolution of organic compounds, so that they can give full play to their own advantages, which is of great significance for the research of electrode materials.

[0004] As an important component of sodium ion positive electrode materials, binders can bond active substances and conductive substances to current collectors. They need to have high viscosity and maintain a complete conductive network during the electrochemical cycle, which directly affects the quality and performance of electrode materials. Therefore, the role of binders cannot be ignored. Polyvinyl fluoride has stable electrochemical properties and is one of the most widely used binders. However, polyvinyl fluoride is usually added in large amounts and is easy to lose its bonding ability in the electrolyte, which has a great impact on the performance of electrode materials. Therefore, it is necessary to improve the binder. The present invention improves organic compounds to prepare nanocomposite active substances and functional binders. The prepared sodium ion battery positive electrode material has high specific capacity, strong rate performance, strong conductivity, and good cycle stability, and has broad application prospects. Summary of the invention

[0005] In order to solve the problems raised in the background technology, the object of the present invention is to provide a sodium ion battery positive electrode material and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A sodium ion battery positive electrode material comprises the following raw materials in parts by weight: 75-85 parts of nano composite active material, 10-15 parts of conductive material, and 5-10 parts of functional binder.

[0008] Furthermore, the preparation method of the nanocomposite active material comprises the following steps:

[0009] Step A, dissolving chitosan in an acetic acid solution to form a chitosan solution, adding the chitosan solution, allyl methyl sulfide and triethylamine into N,N-dimethylformamide, stirring evenly, raising the temperature to 70-90° C., reacting for 8-10 hours, and obtaining modified chitosan;

[0010] Step B, adding modified chitosan and potassium hydroxide to a ball mill, and then adding the ball mill to a ball mill for ball milling for 1-3 hours. After the ball milling is completed, it is transferred to a glass tube furnace, filled with nitrogen protection, heated to 600-800° C. at 4-6° C. / min, and carbonized for 1-3 hours. It is naturally cooled to room temperature, washed, filtered, and dried at 55-65° C. for 4-6 hours to obtain a nitrogen-rich sulfur porous carbon material;

[0011] Step C: Add nitrogen-rich sulfur porous carbon material and 7,7,8,8-tetracyanoquinone dimethane into dimethyl sulfoxide, mix and ultrasonicate for 30-50 minutes, transfer the system to a drying oven, increase the temperature to 110-130° C., and dry for 6-8 hours to obtain a nanocomposite active substance.

[0012] By adopting the above technical scheme, the amino group in chitosan and the alkenyl group in the allyl methyl sulfide structure can undergo Michael addition reaction under the catalytic action of triethylamine to obtain modified chitosan grafted with sulfide, and potassium hydroxide is used as an activator to etch a pore structure on the carbonized modified chitosan to obtain a nitrogen-rich sulfur porous carbon material. The capillary principle is used to allow 7,7,8,8-tetracyanobenzoquinone dimethane to enter the pores of the nitrogen-rich sulfur porous carbon material along with the solvent dimethyl sulfoxide, and finally the dimethyl sulfoxide is evaporated to leave 7,7,8,8-tetracyanobenzoquinone dimethane in the pores to obtain a nano-composite active substance.

[0013] Furthermore, in step A, the mass fraction of the acetic acid solution is 4-5%.

[0014] Furthermore, in step B, the mass ratio of the modified chitosan to potassium hydroxide is 2.5-1.5:1.

[0015] Furthermore, in step C, the mass ratio of the nitrogen-rich sulfur porous carbon material to 7,7,8,8-tetracyanobenzoquinone dimethane is 1:2.5-3.5.

[0016] Furthermore, the preparation method of the functional adhesive comprises the following steps:

[0017] S1. Add 0.8-1.2 mol / L of dilute hydrochloric acid to the tris(hydroxymethyl)aminomethane solution to adjust the pH value to 8-9, add dopamine, stir to dissolve, and then let stand for 1-3 hours until the solution turns brown to obtain polydopamine;

[0018] S2, adding polydopamine, chloroacetaldehyde and glacial acetic acid to N,N-dimethylformamide and mixing them evenly, introducing nitrogen, adjusting the pH, starting stirring, and reacting for 4-6 hours to obtain modified polydopamine;

[0019] S3. Add modified polydopamine to dimethyl sulfoxide, introduce nitrogen, then add polyethylene oxide and acid binding agent and mix well, raise the temperature to 60-80°C, react for 5-8h, and obtain a functional adhesive.

[0020] By adopting the above technical scheme, polydopamine undergoes a Schiff base reaction with the aldehyde group in the chloroacetaldehyde structure, and an active chlorine substituent is introduced into the polydopamine to obtain a modified polydopamine. The chlorine substituent in the modified polydopamine can undergo a substitution reaction with the active hydroxyl group in the polyethylene oxide structure to obtain a functional adhesive. After the two are combined, the structure has a large number of catechol groups and ether bonds, which can produce a strong intermolecular force with the bonded substrate, thereby improving the bonding strength. At the same time, polydopamine has ionic conductivity, and after being grafted with polyethylene oxide, the ionic conductivity is enhanced.

[0021] Furthermore, in S2, the pH value is 4.5-5.5.

[0022] Furthermore, in S3, the acid binding agent is triethylamine or pyridine.

[0023] Furthermore, the conductive material is any one of carbon black, acetylene black or carbon nanotubes.

[0024] A method for preparing a positive electrode material for a sodium ion battery is as follows:

[0025] The nanocomposite active material, the conductive material and the functional binder are added to N-methyl-2-pyrrolidone in parts by weight, and the mixture is placed on a magnetic stirrer and stirred for 2-4 hours to obtain a mixed slurry, which is the positive electrode material for a sodium ion battery.

[0026] Furthermore, the stirring rate is 200-400 r / min.

[0027] Beneficial effects of the present invention:

[0028] (1) The organic compound 7,7,8,8-tetracyano-p-quinone dimethane in the nanocomposite active material prepared by the present invention has a high redox potential, which plays an important role in the specific capacity and cycle stability of the electrode material. Fixing it in the nitrogen-rich sulfur porous carbon material can effectively slow down and inhibit the solubility of the electrolyte in it, ensure that its own advantages are effectively exerted, and improve the specific capacity and cycle stability of the electrode material. At the same time, the nitrogen-rich sulfur porous carbon material ensures the smoothness of the conductive network, increases the specific surface area of ​​the material, shortens the sodium ion transmission distance, and promotes the rapid transmission of sodium ions. The introduction of nitrogen elements in the porous carbon material improves the conductivity of the porous carbon material and increases the number of active sites. The introduction of sulfur elements increases the spacing of the porous carbon material, which is conducive to the insertion and extraction of sodium ions. The nitrogen-rich sulfur porous carbon material improves the conductivity and cycle stability of the nanocomposite active material. The nitrogen-rich sulfur porous carbon material is used to coat 7,7,8,8-tetracyano-p-quinone dimethane to improve the specific capacity, cycle stability and rate performance of the positive electrode material of the sodium ion battery.

[0029] (2) The functional binder prepared by the present invention is obtained by grafting polyethylene oxide with polydopamine, which is environmentally friendly. The functional binder structure contains a large number of catechol groups and ether bonds to improve the bonding performance, and can generate strong intermolecular forces with the bonded substrate. Therefore, only a small amount of binder is needed to bond the nanocomposite active material and the conductive material together, and it is easy to bond with the current collector, avoiding the clogging of the pores of the nanocomposite active material by adding a large amount of binder, resulting in a decrease in the electrochemical performance of the sodium ion battery. In addition, the strong bonding performance of the functional binder is conducive to improving the stability of the overall structure, reducing the interface peeling phenomenon during the charge and discharge process, and extending the service life of the positive electrode material. At the same time, polyethylene oxide has excellent ionic conductivity. After being grafted with polydopamine, the ionic conductivity of the binder is improved, thereby improving the rate performance of the positive electrode material of the sodium ion battery.

[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1 This is an infrared spectrum of the functional adhesive prepared in the example of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] 1. Preparation of Nanocomposite Active Materials

[0036] Step A, dissolving 3.2 g of chitosan in 4.5% acetic acid solution to form a chitosan solution, adding the chitosan solution, 2 g of allyl methyl sulfide and 0.8 g of triethylamine to N,N-dimethylformamide, stirring evenly, raising the temperature to 80° C., reacting for 8 h, and obtaining modified chitosan;

[0037] Step B, adding 2g of modified chitosan and 1g of potassium hydroxide to a ball mill, and then adding the ball mill to a ball mill for 2h. After the ball milling is completed, it is transferred to a glass tube furnace, filled with nitrogen protection, heated to 800°C at 5°C / min, and carbonized for 2h. It is naturally cooled to room temperature, washed, filtered, and dried at 60°C for 5h to obtain a nitrogen-rich sulfur porous carbon material;

[0038] Step C, add 2g of nitrogen-rich sulfur porous carbon material and 5g of 7,7,8,8-tetracyanoquinone dimethane into dimethyl sulfoxide, mix and ultrasonicate for 40min, transfer the system to a drying oven, increase the temperature to 120°C, and dry for 8h to obtain a nanocomposite active substance.

[0039] The nitrogen-rich sulfur porous carbon material was tested using a Var io MACRO cube element analyzer. The test results showed that the nitrogen content in the nitrogen-rich sulfur porous carbon material was 10.23%, and the sulfur content was 6.84%.

[0040] 2. Preparation of functional binder

[0041] S1. Add 1 mol / L of dilute hydrochloric acid to the tris(hydroxymethyl)aminomethane solution to adjust the pH value to 8.5, add 3 g of dopamine, stir to dissolve, and then let stand for 2 hours until the solution turns brown to obtain polydopamine;

[0042] S2, adding 2.5 g polydopamine, 1.6 g chloroacetaldehyde and 1 g glacial acetic acid to N,N-dimethylformamide, mixing evenly, introducing nitrogen, adjusting the pH to 5, starting stirring, reacting for 5 h, and obtaining modified polydopamine;

[0043] S3. Add 2.5 g of modified polydopamine into dimethyl sulfoxide, introduce nitrogen, then add 3 g of polyethylene oxide and 1.2 g of triethylamine and mix well, then raise the temperature to 70°C and react for 8 hours to obtain a functional adhesive.

[0044] The functional binder was mixed with potassium bromide and ground into a film, and then infrared testing was performed using a Fourier transform infrared spectrometer, such as Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of the functional adhesive, 3189cm -1 The absorption peak of carbon and hydrogen on the benzene ring of polydopamine appeared at 2888cm -1 The absorption peak of the methylene group in polyethylene oxide appeared at 1640 cm -1 The absorption peak of Schiff base carbon-nitrogen double bond appears at 1100 cm -1 The absorption peak of ether bond appears at

[0045] Peel test: Use BT1-FR010TH.A50 universal testing machine to perform a 180° peel test on the aluminum foil coated with polydopamine and functional adhesive on one side. Attach the aluminum foil coated with polydopamine and functional adhesive on one side to 3M tape, and affix double-sided tape on the other side of the aluminum foil and fix it on a glass slide to test the bonding performance, as shown in the following table:

[0046] Polydopamine Functional adhesive <![CDATA[Peeling force / Ncm -1 > 1.25 3.03

[0047] It can be seen from the above table that the bonding performance of the functional adhesive is better than that of polydopamine. After polydopamine is grafted with polyethylene oxide, the number of binding sites with the adhered substrate is increased. The large number of catechol groups and ether bonds in the structure can produce strong intermolecular forces with the adhered substrate, thereby enhancing the bonding performance of the functional adhesive.

[0048] 3. Preparation of positive electrode materials for sodium ion batteries

[0049] 75 g of nanocomposite active material, 15 g of carbon black and 10 g of functional binder were added to N-methyl-2-pyrrolidone and mixed, and the mixture was placed on a magnetic stirrer and stirred at a stirring rate of 200 r / min for 2 h to obtain a mixed slurry, which is the positive electrode material for a sodium ion battery.

[0050] Example 2

[0051] Preparation of positive electrode materials for sodium ion batteries

[0052] 80 g of nanocomposite active material, 15 g of carbon black and 5 g of functional binder were added to N-methyl-2-pyrrolidone and mixed, and the mixture was placed on a magnetic stirrer and stirred at a stirring rate of 300 r / min for 3 h to obtain a mixed slurry, which is the positive electrode material for a sodium ion battery.

[0053] The preparation method of the nanocomposite active material and the functional binder is the same as that in Example 1.

[0054] Example 3

[0055] Preparation of positive electrode materials for sodium ion batteries

[0056] 85 g of nanocomposite active material, 10 g of carbon black and 5 g of functional binder were added to N-methyl-2-pyrrolidone and mixed, and the mixture was placed on a magnetic stirrer and stirred at a stirring rate of 400 r / min for 4 h to obtain a mixed slurry, which is the positive electrode material for a sodium ion battery.

[0057] The preparation method of the nanocomposite active material and the functional binder is the same as that in Example 1.

[0058] Comparative Example 1

[0059] Preparation of positive electrode materials for sodium ion batteries

[0060] 80 g of nanocomposite active material, 15 g of carbon black and 5 g of polyvinyl fluoride were added to N-methyl-2-pyrrolidone and mixed, and the mixture was placed on a magnetic stirrer and stirred at a stirring rate of 300 r / min for 3 h to obtain a mixed slurry, which is the positive electrode material for a sodium ion battery.

[0061] The preparation method of the nanocomposite active material is the same as that in Example 1.

[0062] Comparative Example 2

[0063] Preparation of positive electrode materials for sodium ion batteries

[0064] 80 g of 7,7,8,8-tetracyanobenzoquinone dimethane, 15 g of carbon black and 5 g of a functional binder were added to N-methyl-2-pyrrolidone and mixed, and the mixture was placed on a magnetic stirrer and stirred at a stirring rate of 300 r / min for 3 h to obtain a mixed slurry, which is a positive electrode material for a sodium ion battery.

[0065] The preparation method of the functional adhesive is the same as that in Example 1.

[0066] Test example

[0067] The sodium ion battery positive electrode materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 and 2 are uniformly coated on aluminum foil, and then placed in a vacuum drying oven for drying to form a positive electrode sheet. Metallic sodium is used as a negative electrode, glass fiber is used as a separator, and 1.0M NaClO4 is used as a liquid electrolyte. In a sodium ion battery glove box, a battery is assembled in the order of metallic sodium, electrolyte, glass fiber separator, electrolyte, and positive electrode sheet. The battery is taken out and sealed on a sub-sealing machine to obtain a button battery.

[0068] Electrochemical test: Electrochemical tests were conducted on button cells made of different cathode materials in each group. The initial specific capacity test conditions were: 0.1C, 2-4.5V; the cycle performance test conditions were 0.1C, 100 weeks at room temperature; the rate performance test conditions were 1C test for 100 weeks. The results are shown in the following table:

[0069]

[0070] It can be seen from the above table that the sodium ion battery positive electrode materials prepared in Examples 1 to 3 of the present invention have excellent cycle stability, rate performance and high specific capacity. In Comparative Example 1, polyvinyl fluoride is added as a binder, and a small amount of addition leads to insufficient bonding performance, and interfacial peeling may occur during the cycle, and polyvinyl fluoride has poor ionic conductivity, so the test results are poor; Comparative Example 2 adds 7,7,8,8-tetracyanobenzoquinone dimethane as an active substance, and cannot utilize nitrogen-rich sulfur porous carbon material coating to enhance conductivity, increase the number of active sites, and improve cycle stability and rate performance, and a certain amount of dissolution occurs in the electrolyte during the cycle, so the test results are poor.

[0071] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A sodium ion battery positive electrode material, characterized in that: The invention comprises the following raw materials in parts by weight: 75-85 parts of nano composite active material, 10-15 parts of conductive material and 5-10 parts of functional adhesive.

2. A sodium ion battery positive electrode material according to claim 1, characterized in that: The preparation method of the nanocomposite active material comprises the following steps: Step A, dissolving chitosan in an acetic acid solution to form a chitosan solution, adding the chitosan solution, allyl methyl sulfide and triethylamine into N,N-dimethylformamide, stirring evenly, raising the temperature to 70-90° C., reacting for 8-10 hours, and obtaining modified chitosan; Step B, adding modified chitosan and potassium hydroxide to a ball mill, and then adding the ball mill to a ball mill for ball milling for 1-3 hours. After the ball milling is completed, it is transferred to a glass tube furnace, filled with nitrogen protection, heated to 600-800° C. at 4-6° C. / min, and carbonized for 1-3 hours. It is naturally cooled to room temperature, washed, filtered, and dried at 55-65° C. for 4-6 hours to obtain a nitrogen-rich sulfur porous carbon material; Step C: Add nitrogen-rich sulfur porous carbon material and 7,7,8,8-tetracyanoquinone dimethane into dimethyl sulfoxide, mix and ultrasonicate for 30-50 minutes, transfer the system to a drying oven, increase the temperature to 110-130° C., and dry for 6-8 hours to obtain a nanocomposite active substance.

3. A sodium ion battery positive electrode material according to claim 2, characterized in that: In step A, the mass fraction of the acetic acid solution is 4-5%.

4. A sodium ion battery positive electrode material according to claim 2, characterized in that: In step B, the mass ratio of the modified chitosan to potassium hydroxide is 2.5-1.5:

1.

5. A sodium ion battery positive electrode material according to claim 2, characterized in that: In step C, the mass ratio of the nitrogen-rich sulfur porous carbon material to 7,7,8,8-tetracyanobenzoquinone dimethane is 1:2.5-3.

5.

6. A sodium ion battery positive electrode material according to claim 1, characterized in that: The preparation method of the functional binder comprises the following steps: S1. Add 0.8-1.2 mol / L dilute hydrochloric acid to the tris(hydroxymethyl)aminomethane solution to adjust the pH value to 8-9, add dopamine, stir to dissolve, and then stand for 1-3 hours until the solution turns brown to obtain polydopamine; S2, adding polydopamine, chloroacetaldehyde and glacial acetic acid to N,N-dimethylformamide and mixing them evenly, introducing nitrogen, adjusting the pH, starting stirring, and reacting for 4-6 hours to obtain modified polydopamine; S3. Add modified polydopamine to dimethyl sulfoxide, introduce nitrogen, then add polyethylene oxide and acid binding agent and mix well, raise the temperature to 60-80°C, react for 5-8h, and obtain a functional adhesive.

7. A sodium ion battery positive electrode material according to claim 6, characterized in that: In S2, the pH value is 4.5-5.

5.

8. A sodium ion battery positive electrode material according to claim 6, characterized in that: In S3, the acid binding agent is triethylamine or pyridine.

9. A sodium ion battery positive electrode material according to claim 1, characterized in that: The conductive material is any one of carbon black, acetylene black or carbon nanotubes.

10. A method for preparing a positive electrode material for a sodium ion battery as claimed in claim 1, characterized in that: As shown below: The nanocomposite active material, the conductive material and the functional binder are added to N-methyl-2-pyrrolidone in parts by weight, and the mixture is placed on a magnetic stirrer and stirred for 2-4 hours to obtain a mixed slurry, which is the positive electrode material for a sodium ion battery.

11. The method for preparing a positive electrode material for a sodium ion battery according to claim 10, characterized in that: The stirring rate is 200-400r / min.